(untitled) (Research, Society and Development, 2021)
Objective: Narrate the multiprofessional experience in research using medical records to insert the data in the RESCOVID platform. Methodology: This is a descriptive research with a qualitative approach of the type of experience report, carried out in a public health hospital in the city of Fortaleza-Ceará. The reported experience occurred during the period from May 2020 to April 2021 in a prospective collection performed by a multiprofessional team participating in the project entitled “An electronic medical record system for patients hospitalized with COVID-19 in a reference hospital in Ceará - ResCOVID ”. Results and discussion: The experiences lived by the collectors highlight main difficulties found in the data collection such as of data, inconsistency of data, patients without a diagnostic test for COVID-19, data collection method and fear of infection due to the research site. Final considerations: The results found through the experience reported in this study reinforce the importance of the constant search for the development of innovations and improvements in the resources to do research, in the resources to do research. In addition, even in face of structural limitations, these advances in the investigation process may bring agility and reliability to the scope of data collection.